Pengaruh Metode Cooperative Scrift dan Peran Orang Tua Terhadap Prestasi Belajar Bahasa Indonesia - Sigit Widiyarto (Universitas Muhammadiyah Purwokerto, 2018)
Abstract Learning methods in the schools can determine the success students. But Mastery learning method is still less optimal. One of method to increase student activity is cooperatif scrift. This research used experimental method. The research findings: There is the effect of the method cooperatif scrift to achievement learn Indonesian. By using scrift Coopertif method can improve student achievement, so that better and proper administration of these methods will increase student learning outcomes. There is the influence of the role of parents to the student achievement Indonesian. The role of parents can improve student achievement. The role of parents is very important to support the child in improving learning achievement in school. There is the influence of cooperatif scrift methods and the role of parents simultaneously to achievement learn Indonesian. Provision of appropriate methods target will create an optimal learning process. The role of parents both at home and at school can support better result. Keywords: cooperative scrift method, Role of Parents and The result of Bahasa Learning